PUBLIC ADMINISTRATION OF INNOVATIVE TOURISM DEVELOPMENT: MODERN TYPES AND INNOVATIVE TECHNOLOGIES - Krutii А. M. (Theory and Practice of Public Administration, 2021)
The current stage of development of the world is characterized by the introduction of new technologies, processes of informatization and digitalization in all spheres of social development, tourism as well. The development of the tourism sector is extremely important for Ukraine. It is possible to ensure the return of this potential only under the condition of public management of innovative development of tourism, application of modern types and innovative technologies of tourism organization, introduction of effective mechanisms of public management, attraction of qualified personnel. However, despite the significant number of scientific developments on the introduction of innovations in the tourism sector, there is a need for further study of public management of the use of innovative technologies in tourism. The purpose of the article. The purpose of this work is to substantiate the need for research on public management of innovative tourism development to reveal its potential opportunities for the country’s development The emergence of unforeseen circumstances related to the COVID-19 pandemic has changed the situation not only in the tourism sector, but also in the world as a whole. This situation in the world is a confirmation of the need for public management of the introduction of innovations in tourism, which should be perceived as a constant, global and dynamic process, and tourism innovation should be in the form of new ideas, processes, types and technologies. Therefore, one of the directions of development of the tourism industry in Ukraine is the introduction of its innovative forms and technologies. The term “innovation” comes from the Latin word “innovatio”, which means the creation of something new. The variety of definitions lies in the different purposes of studying this phenomenon. An integrated approach takes into account when defining this concept (according to Schumpeter (1997) four areas in which innovations are implemented: 1) the creation of new or improved products; 2) introduction of new production processes; 3) development of new markets; 4) reorganization of the company. Currently, researchers focus on the need and importance of innovation to achieve competitive advantage (improvement of public services, processes, methods, procedures) in the tourism sector. Modern innovative practices are available in the tourism sector around the world as part of intelligent technology. The long-term development of these technologies, the emergence of new ideas and methods in the tourism market are important for its future. Intelligent technologies facilitate business communication, reduce working time. However, it also has certain threats, such as the disappearance of some professions. Therefore, it is necessary to pay attention to the need for qualified personnel in tourism, which, despite the introduction of automated technologies, remains a labor-intensive area. As for Ukraine, innovative technologies are important from the standpoint of solving urgent problems in the tourism industry (increasing the level of service, improving the material and technical base, preservation of cultural monuments, etc.). Therefore, it is expedient to allocate such types of innovative technologies which are applied in tourist sphere of our country: on sphere of novelty; by content (organizational and managerial, informational, technological, technical); due to the occurrence (reactive and strategic); by potential (radical and modifying). According to this classification, Internet technologies will belong to information innovation technologies that can be used in several areas. Therefore, it is important that the tourism sector should become part of the national humanitarian policy and priorities, taken into account when considering other issues of national importance. The implementation of the measures mentioned in the study will increase the efficiency of public management of tourism development, pursue an active regional policy in the field of tourism, ensure coordination of activities of local executive bodies, local governments and businesses.